PENGARUH KEPERCAYAAN atas MERK TERHADAP LOYALITAS NASABAH pada BANK BTPN PURNA BAKTI KCP KABANJAHE - Charisma Kuriata Ginting S (JURNAL REGIONOMIC, 2018)
The purpose of research is to determine the extent of the influence of brand truston customer loyalty to the Bank BTPN KCP Purna Bakti Kabanjahe.The author believesthat the company to be able to withstand the competition is to maintain confidence in thebrand to remain strong in mind and in accordance with customer expectations, so that initself creates loyalty to the brand owner.The indicators used to measure customer loyalty due to confidence in the brand,namely: a repeat purchase on a particular brand, the habit of consuming certain brands,a pleasure on a particular brand, steadiness on specific brands, assuming the specificbrand is the best and recommend a particular brand to othersThe results showed the model of linear regression equation Y = 11.962 + 0,605X,with very significant t-test and test of determination R2 = 0.427. The conclusion ofconfidence on the brand has a significant positive effect on customer loyalty amounted to42.7%, and the remaining 57.3% is determined by other factors.